Fraser & Murray, America And The World Since 1945 - Cole, Jeffrey (Teaching History: A Journal of Methods, 2005)
Historians Fraser and Murray provide a concise overview of United States foreign policy and its consequences using presidential administrations as the organizational rubric for their textbook. Beginning with Harry S Truman and the onset of the Cold War and ending with the challenges the second Bush administrative faced beginning on September 11, 2001, the authors take the reader through the second half of the twentieth century in a methodical, well-organized manner. Except for Truman and Richard M. Nixon who receive two chapters ("Truman and the Coming of the Cold War," "Truman and the Crystallisation of the Cold War," "Nixon: The Peacemaker?" and "Nixon, Ford and the American Crisis") and Gerald R. Ford who shares one with Nixon, each post-war chief executive is allotted a single chapter.